Unifying the Aminohexopyranose‐ and Peptidyl‐Nucleoside Antibiotics: Implications for Antibiotic Design. (11th May 2020) - Serrano, Catherine M.; Kanna Reddy, Hariprasada Reddy; Eiler, Daniel; Koch, Michael; Tresco, Ben I. C.; Barrows, Louis R.; VanderLinden, Ryan T.; Testa, Charles A.; Sebahar, Paul R.; Looper, Ryan E.
Abstract: In search of new anti‐tuberculars compatible with anti‐retroviral therapy we re‐identified amicetin as a lead compound. Amicetin's binding to the 70S ribosomal subunit of Thermus thermophilus ( Tth ) has been unambiguously determined by crystallography and reveals it to occupy the peptidyl transferase center P‐site of the ribosome. The amicetin binding site overlaps significantly with that of the well‐known protein synthesis inhibitor balsticidin S. Amicetin, however, is the first compound structurally characterized to bind to the P‐site with demonstrated selectivity for the inhibition of prokaryotic translation. The natural product‐ribosome structure enabled the synthesis of simplified analogues that retained both potency and selectivity for the inhibition of prokaryotic translation. Abstract : Oldies but goodies : Amicetin, first isolated in the 1950s is demonstrated to be the first prokaryotic‐selective inhibitor of the ribosomal P‐site. Simplification of amicetin's structure provides compounds with comparable biochemical and whole‐cell activity against Mycobacterium tuberculosis . Given this selectivity, lack of cytotoxicity and dramatic structural changes that can be tolerated, amicetin holds promise as an anti‐tubercular lead.